2010
DOI: 10.1152/ajpheart.01280.2008
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of myocardial injury in mice with functional deletion of the circadian rhythm gene mPer2

Abstract: Virag JA, Dries JL, Easton PR, Friesland AM, DeAntonio JH, Chintalgattu V, Cozzi E, Lehmann BD, Ding JM, Lust RM. Attenuation of myocardial injury in mice with functional deletion of the circadian rhythm gene mPer2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 49 publications
(56 reference statements)
2
43
1
1
Order By: Relevance
“…16 Per2 was selected for analysis, given that it is regulated by aldosterone in cardiomyocytes and that mice null for Per2 are protected from cardiac remodeling. 17 Per2 was upregulated at 8 days of DOC/salt in WT but not MyoMRKO mice, suggesting a potential role for cardiomyocyte MR signaling in the modulation of clock genes, although detailed time-course studies are required to fully characterize this response. Given that the cardiomyocyte circadian clock influences myocardial gene expression, heart rate, function, and tolerance to reperfusion injury, Per2 may represent a novel contributor to DOC/ salt-mediated cardiac pathology.…”
Section: Cardiomyocyte Mr and Collagen Depositionmentioning
confidence: 99%
“…16 Per2 was selected for analysis, given that it is regulated by aldosterone in cardiomyocytes and that mice null for Per2 are protected from cardiac remodeling. 17 Per2 was upregulated at 8 days of DOC/salt in WT but not MyoMRKO mice, suggesting a potential role for cardiomyocyte MR signaling in the modulation of clock genes, although detailed time-course studies are required to fully characterize this response. Given that the cardiomyocyte circadian clock influences myocardial gene expression, heart rate, function, and tolerance to reperfusion injury, Per2 may represent a novel contributor to DOC/ salt-mediated cardiac pathology.…”
Section: Cardiomyocyte Mr and Collagen Depositionmentioning
confidence: 99%
“…Analyses of gene expression profiles revealed that Ͼ10% of myocardial genes exhibit circadian rhythms (58). Recently, Virag et al (54) reported that functional deletion of the Per2 gene in knockout mice significantly reduced the size of MI. In the current study, we observed that expression of Per2 gene is downregulated, while Arntl gene expression is increased in transgenic Cd36-SHR compared with SHR controls, which suggests that the repressor activity of Per2 is reduced and thus its targets might be upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…13 Studies by Virag et al showed that mPer2 mutant (functional null) mice have reduced infarct by 43% after nonreperfused MI, by 69% after ischemia/ reperfusion, and by 75% after preconditioned ischemia/ reperfusion, respectively. 15,16 However, Eckle et al found that mPer2 mutant mice had larger infarct sizes and loss of the cardioprotection conferred by ischemic preconditioning when compared with wild-type mice. 100 The same group also found a reduction in infarct size at ZT12 and ZT18 compared with ZT0, which is different from the first report by Durgan et al 13 Although different surgical techniques and protocols (time-of-day) were used and may have contributed to the different results, more studies are needed to elucidate the reasons for this discrepancy.…”
Section: Ischemia/reperfusionmentioning
confidence: 99%
“…[5][6][7][8] In addition, disruption of the circadian rhythm either in the brain (central clock) or in the peripheral tissues (peripheral clock) leads to cardiovascular disease in both human and animal models. [9][10][11][12][13][14][15][16][17][18][19] In this review, we summarize our current understanding of the interplay between circadian regulation and cardiovascular disease, as well as future directions in development of therapy.…”
Section: Introductionmentioning
confidence: 99%